Base cations, K+ and Ca2+, have contrasting effects on soil carbon, nitrogen and denitrification dynamics as pH rises. (October 2017) - Anderson, C.; Peterson, M.; Curtin, D.
Abstract: Full denitirifcation of NO3 − to N2 is most likely when soil pH is elevated and oxygen levels are low. In the period immediately following urine deposition, soil pH and dissolved organic carbon (DOC) concentrations rapidly increase, coupled with O2 consumption - conditions conducive to denitrification and gaseous N-loss - yet the potential for rapid denitrification during this early period post urine deposition has received little attention. In addition, recent research has shown that the amount of DOC (and N) released as pH increases is affected by the valence of the accompanying base cation, with monovalent cations releasing more. Liming has been used to positively influence N2 O/(N2 O + N2 ) ratios in the later stages of N-transformations post urine deposition, yet the relative amounts of DOC (and N) released is likely to be affected in the presence of divalent Ca 2+ potentially lowering N-transformation potential. Soil pH in anaerobic microcosms was adjusted to values between 4.5 and 9.5 using either Ca(OH)2 as a liming agent, or KOH as an analog of urine derived NH4 OH. After 16 h incubation, up to ∼6800 μg g −1 of DOC and ∼480 μg g −1 of dissolved organic nitrogen (DON) was solubilized by KOH amendment which was ∼10-fold higher than Ca(OH)2 ammendment, while NH4 + and NO3 − increased to concentrations well above native soil concentrations. In Ca(OH)2 amended microcosms, denitrification enzyme activity (DEA) assays produced a maximum of 875 ng N2 O-N g −1 h −1 at pH 7.2 with respiration rates <10 μg CO2 -C g −1 h −1 . In contrast, DEA and respiration continually climbed in KOH amended microcosms with rates up to 4798 ng N2 O-N g −1 h −1 and 47 μg CO2 -C g −1 h −1 at pH 8.7 and 8.9, respectively. By using KOH as proxy for NH4 OH derived from urea hydrolysis, this research has shown that rapid denitrification could occur shortly after urine deposition along with substantial DOC and DON solubilisation and N-mineralisation. However, elevated soil pH combined with excess Ca 2+ from liming might actually suppress denitrification potential. We propose that excess Ca 2+ affects how soil microbes access and process DOC and DON at elevated pH, with Ca 2+ acting to stabilize DOC and DON. Our results emphasize that although liming promotes soil conditions conducive to denitrification, DEA can be markedly affected by base type and prevailing soil chemical conditions. Highlights: Anaerobic alkaline conditions with excess Ca 2+ ions inhibits denitrification. Anaerobic alkaline conditions with excess K + ions promotes denitrification. Denitrification increases concomitantly with dissolved organic matter (DOM). With K +, organic N mineralisation is required to supply extra NH4 + and NO3 − Proposed mechanism is that Ca 2+ affects accessibility and processing of DOM.